PENGARUH CUSTOMIZATION, CONTACT INTERACTIVITY, CULTIVATION, COMMUNITY, CHOICE, CONVENIENCE, CHARACTER TERHADAP E-LOYALTY CUSTOMER DI SITUS KASKUS - HENDRIAN, DENNY LUKAS (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this research is: to test the influence of customization, contact interactivity, cultivation, community choice, convenience, character of E-Loyalty Customer in Kaskus Site. This research uses primary data to the population of 150 respondents ever shopping at Kaskus Site at least twice. While the data samples that used in this study of 150 respondents aged between 18-50 years and Had done shopping at the site of kaskus at least twice. The hypothesis in this study mentions that the customization, contact interactivity, cultivation, community choice, convenience, character have an influence on the E-Loyalty Customer. The test results by multiple linear regression analysis model that significantly explains the customization, contact interactivity, cultivation, community, choice, convenience, character have a positive influence of E-Loyalty Customer.